Designing a Dy-2 Single-Molecule Magnet with Two Well Differentiated Relaxation Processes by Using a Nonsymmetric Bisbidentate Bipyrimidine-N-Oxide Ligand: A Comparison with Mononuclear Counterparts - Aravena-Ponce, D; Aravena-Ponce, D (American Chemical Society, 2018)
Herein we report a dinuclear [(N-mbpymNO)-{(tmh)(3)Dy}(2)] (1) single-molecule magnet (SMM) showing two nonequivalent Dy-III centers, which was rationally prepared from the reaction of Dy(tmh)(3) moieties (tmh = 2,2,6,6-tetramethyl-3,5-heptanedionate) and the asymmetric bis-bidentate bridging ligand 4-methylbipyrimidine (mbpymNO). Depending on whether the Dym ions coordinate to the NAO or NAN bidentate donor sets, the Dym sites present a NO7 (D2d geometry) or N206 (D4d) coordination sphere. As a consequence, two different thermally activated magnetic relaxation processes are observed with anisotropy barriers of 47.8 and 54.7 K. Ab initio calculations confirm the existence of two different relaxation phenomena and allow one to assign the 47.8 and 54.7 K energy barriers to the Dy(N2O6) and Dy(NO7) sites, respectively. Two mononuclear complexes, [Dy(tta)3(mbpymNO)] (2) and [Dy(tmh)3(phenNO)] (3), have also been prepared for comparative purposes. In both cases, the Dym center shows a NO7 coordination sphere and SMM behavior is observed with [Jeff values of 71.S K (2) and 120.7 K (3). In all three cases, ab initio calculations indicate that relaxation of the magnetization takes place mainly via the first excited-state Kramers doublet through Orbach, Raman, and thermally assisted quantum-tunnelling mechanisms. Pulse magnetization measurements reveal that the dinuclear and mononuclear complexes exhibit hysteresis loops with double- and single-step structures, respectively, thus supporting their SMM behavior.